4D printing of self-immolative polymers - Markhart, Johannes; Mainik, Philipp; Klee, Pia S.; Blasco, Eva (Advanced functional materials, 2025)
4D printing has emerged as a powerful technique for fabricating complex 3D structures that evolve over time in response to external stimuli. In particular, “living” 4D printing strategies enable dynamic, reversible modulations of material properties such as size and mechanical stiffness via post-printing chemical modifications. However, current systems suffer from slow response times and limited reversibility, which restrict their practical applications. Herein, a new approach is presented to address these limitations by integrating self-immolative polymers (SIPs) with light-based 3D printing. These polymers are programmed to undergo complete depolymerization in response to an external stimulus, providing a unique mechanism of “living” degrowth that expands the toolbox of adaptive transformations. To this aim, photopolymerizable SIPs consisting of silyl end-capped poly-o-phthalaldehyde are synthesized on the multi-gram scale and employed in inks for digital light processing. Upon exposure to fluoride ions, which cleave the silyl end-caps, rapid depolymerization of the polymers results in significant degrowth of fabricated objects, accompanied by modulations of mechanical stiffness and optical transparency. Subsequent repolymerization enables regrowth of the objects. This study establishes SIPs as a platform for 4D printing and lays the groundwork for future development of dynamic, reconfigurable systems.
Zuerst veröffentlicht: 02. November 2025
Gesehen am 02.12.2025